Analisis Sistem Penyangga pada Terowongan Pengelak Proyek Bendungan Lau Simeme Kec. Sibiru-biru Kabupaten Deli Serdang, Sumatera Utara - Geovano Osvaldo Simbolon; Nurmaidah Nurmaidah (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2023)
This tunnel is an alternative structure used to divert river water during construction of the dam body. Location The tunnel is located in Kuala Deca Village, Civilville District, Deli Serdang District, North Sumatra. Since this tunnel is located under a hill, a buffer system is required within the tunnel for the tunnel to be considered safe. The purpose of this study is to analyze the entrance side stress and calculate the safety factor of the tunnel. Rock mass classification (RMR) is currently used to determine the service life of tunnels. Analysis of the upstream support system